GAMBARAN MATURASI TULANG KARPAL DAN SERVIKAL PADA PASIEN ORTODONTI USIA 9-18 TAHUN (Studi foto karpal dan sefalometri) - Retno Widayati; Haru Setyo Anggani; Permana Irmansyah Masbirin (Faculty of Dentistry, Universitas Indonesia, 2015)
Children development stage is determined by physical growth. The sequence of growing process is usually constant, however, the age at which children can reach a certain sequence varies individually. Determining skeletal maturation by evaluating carpal bone and cervical vertebrae is very helpful in conducting orthodontic diagnosis and in planning proper treatment. Such evaluation enables to estimate the time of growing process to accelerate or decelerate. The purpose of this study is to evaluate the stage of carpal bone and cervical vertebrae maturation in orthodontic patients at the age of 9 to 18. Samples were 83 cephalograms and hand wrist x-ray from 52 girls and 31 boys. The result of this study showed that the stage of carpal bone and cervical vertebrae maturation in girls and boys in the same age group varies greatly. Girls at the age of 11 to 12 demonstrated highest variation in the stage of maturation. In the same age group of sample, all stages of the maturation indicator were found, such as epiphysis is as wide as diaphysis, the capping of epiphysis, as well as variation in epiphysis fusion. These kinds of variations also occurred in the cervical vertebrae maturation stage, where it varies from cervical vertebrae stage 2 to 6. On the other hand, boys showed highest variation at the age of 13 to 14. This study suggests that there was a matching pattern between carpal bone and cervical vertebrae maturation.